Design and development of palm oil ester-based nanocosmeceuticals - Ng, Sook Han (2012)
Palm oil esters (POEs), esters derived from palm oil and oleyl alcohol have great potential in the cosmetic and pharmaceutical industries due to the excellent wetting behavior of the esters without the oily feel. Nonionic based emulsifiers such as polyoxyethylene sorbitan monostearate (Tween 60), polyoxyethylene sorbitan monooleate (Tween 80) and polyoxyethylene sorbitan trioleate (Tween 85) are widely used in the application of cosmetic products. These nonionic surfactants have excellent safety, mildness and effectiveness. Phase behaviors of palm oil esters were determined through the construction of ternary phase diagrams using nonionic surfactants. The increase of Hydrophilic Lipophilic Balance (HLB) value of the surfactants gave larger homogeneous and isotropic region in ternary phase diagrams. Three types of nonionic surfactants were selected, namely, Tween 60, Tween 80 and Tween 85. Phase diagrams of POEs: Tocotrienol/ T60/ water, POEs: Tocotrienol/T80/water and POEs: Tocotrienol/ T85/water systems were constructed at room temperature. The results showed that the POEs:Tocotrienol/T80/water system gave better performance than the other two individual surfactant systems. It was observed that the POEs: Tocotrienol/ T80/water system exhibited better solubility of water to produce a larger isotropic region as compared to the other system. Solubilisant gamma, a type of co-surfactant was added in the ternary phase diagram of POEs:Tocotrienol/T80/water system. The ratio of 1:0.5 of POEs + Tocotrienol: solubilisant gamma was selected in contribution for enlargement of the isotropic region. Furthermore, as the regions moved to high oil content compositions, more homogeneous regions were observed as compared to single surfactant. Binary surfactants showed better mixing between components and hence better stability. Compositions from the ternary phase diagrams were selected as pre-formulated emulsions. The emulsions were then subjected to rotor-stator, followed by ultrasound cavitation to obtain nano-size emulsions. Nanoemulsions with 10%,20% and 30% (w/w) oil phase concentration were chosen for further studies. The influence of oil and surfactant concentrations to the stability and rheological behavior of the palm oil esters stabilized with nonionic surfactant was evaluated. The stability of the nanoemulsions system was examined with respect to the mean droplet size and zeta potential for over 3 months. The increase in oil phase concentration from 10 to 30% (w/w) showed no distinct changes in the particle size. This indicated the nanoemulsions were stable regardless of the emulsifiers’ types used. The rheological property of nanoemulsions was investigated using oscillatory measurements and viscometry test. The droplet size of the nanoemulsions was found to decrease with the increase in the oil and surfactant concentrations which give effect on the viscosity and yield stress of the nanoemulsions. The flow curve of the emulsions exhibited shear thinning behavior and obeys the Power Law viscosity. The Power Law Index was found to be decreased when the oil, surfactant concentrations and acoustic amplitudes were increased due to the smaller droplet size and narrower size distribution. The dynamic properties of the nanoemulsions were also affected by the oil and surfactant content which indicated stronger structural integrity and greater interdroplets interactions. The viscoelasticity of the nanoemulsions was enhanced by the increase in the oil and surfactant concentrations. The nanoemulsions with higher oil phase concentration (30% (w/w)) showed greater elasticity which implied strong dynamic rigidity of the nanoemulsion. It was the most stable with longest shelf-life. All the formulations were stable after undergoing thaw cycles test, storage at room temperature and 45°C for more than 4 months. The stable nanoemulsions also showed sedimentation rates at earth gravity of 5.2, 3.0 and 2.6 mm/month for 10%, 20% and 30% (w/w) oil phase,respectively. The TGA thermograms showed two major weight losses due to the evaporation of water content and destruction of oil phase. The palm oil esters nanoemulsions containing tocotrienol gave higher Trolox Equivalent Antioxidant Capacity (TEAC) values which implied higher antioxidant capability. Nanoemulsion with 10%, 20% and 30% (w/w) oil phase concentration showed an antimicrobial effect against selected microorganisms and fungal growth.